The Boundaries of Scriptural Cognition. The Examination of śruta-jñāna in its relation to mati-jñāna on the basis of Tattvârtha-sūtra-rāja-vārttika by Akalaṅka - Glinicka, Małgorzata Barbara (Folia Philosophica, 2019)
The aim of the article is to analyze the chosen passages of Akalaṅka’s Tattvârtha-sūtra-rāja-vārttika (8th c. CE) (mainly RVār 1.9, 20 and 26) in order to find an answer to a question: what are the boundaries of śruta-jñāna (‘scriptural cognition’), especially with reference to mati-jñāna’s (‘sensory cognition’) way of functioning? It aims at indicating particular aspects of relation between these two cognitions, basically the cause and effect order, the overlapping scopes of these two cognitions, a possibility of their erroneousness and various means of their attainment. These four issues could be taken into consideration in order to feature both of them in their mutual references. I attach the short analysis of Jinabhadra Gaṇi’s (6/7th c. CE) Viśeṣâvaśyaka-bhāṣya’s passages to shed light, in contrast, on the other Jain text – anteceding Akalaṅka’s treatise – in which this issue has been undertaken and thus to reveal rudimentary cohesion and coherence within the Jain system of thought.